The adenosine A2B receptor drives osteoclast-mediated bone resorption in hypoxic microenvironments - Knowles, H (MDPI, 2019)
Osteoclast-mediated bone destruction is amplified in the hypoxic synovial microenvironment of rheumatoid arthritis (RA). This increased bone resorption is driven by the hypoxia-inducible transcription factor HIF. We identified hypoxic induction of the HIF-regulated adenosine A2B receptor in primary human osteoclasts (mRNA, 3.8-fold increase, p < 0.01) and sought to identify the role(s) of purinergic signaling via this receptor in the bone resorption process. Primary human osteoclasts were differentiated from CD14+ monocytes and exposed to hypoxia (2% O2) and A2B receptor inhibitors (MRS1754, PSB603). The hypoxic increase in bone resorption was prevented by the inhibition of the A2B receptor, at least partly by the attenuation of glycolytic and mitochondrial metabolism via inhibition of HIF. A2B receptor inhibition also reduced osteoclastogenesis in hypoxia by inhibiting early cell fusion (day 3-4, p < 0.05). The A2B receptor is only functional in hypoxic or inflammatory environments when the extracellular concentrations of adenosine (1.6-fold increase, p < 0.05) are sufficient to activate the receptor. Inhibition of the A2B receptor under normoxic conditions therefore did not affect any parameter tested. Reciprocal positive regulation of HIF and the A2B receptor in a hypoxic microenvironment thus enhances glycolytic and mitochondrial metabolism in osteoclasts to drive increased bone resorption. A2B receptor inhibition could potentially prevent the pathological osteolysis associated with hypoxic diseases such as rheumatoid arthritis.